Hubungan antara Konsep Diri dengan Kemampuan Adaptasi Komunikasi pada Mahasiswa Baru Universitas Muhammadiyah Sidoarjo - Akhmad Kholis; Nurfi Laili (EduInovasi: Journal of Basic Educational Studies, 2025)
This research was conducted because there is a problem of communication adaptability in new students at Muhammadiyah University of Sidoarjo. Communication adaptation is a form of individual adjustment in interacting with other individuals. One of the factors that influence communication adaptability is self-concept which is defined as an individual's perception of himself. The sample of this research is new students of Muhammadiyah University of Sidoarjo in 2023 totaling 339 people. The results showed that there was a relationship between self-concept and communication adaptability in new students with a correlation coefficient of 0.420 and a significance value (p) of 0.001.